Delayed KCNQ1/KCNE1 assembly on the cell surface helps IKs fulfil its function as a repolarization reserve in the heart. (1st June 2021) - Wilson, Zachary T.; Jiang, Min; Geng, Jing; Kaur, Sukhleen; Workman, Samuel W.; Hao, Jon; Bernas, Tytus; Tseng, Gea‐Ny
Abstract : Key points: In adult ventricular myocytes, the slow delayed rectifier ( I Ks ) channels are distributed on the surface sarcolemma, not t‐tubules. In adult ventricular myocytes, KCNQ1 and KCNE1 have distinct cell surface and cytoplasmic pools. KCNQ1 and KCNE1 traffic from the endoplasmic reticulum to the plasma membrane by separate routes, and assemble into I Ks channels on the cell surface. Liquid chromatography/tandem mass spectrometry applied to affinity‐purified KCNQ1 and KCNE1 interacting proteins reveals novel interactors involved in protein trafficking and assembly. Microtubule plus‐end binding protein 1 (EB1) binds KCNQ1 preferentially in its dimer form, and promotes KCNQ1 to reach the cell surface. An LQT1‐associated mutation, Y111C, reduces KCNQ1 binding to EB1 dimer. Abstract: Slow delayed rectifier ( I Ks ) channels consist of KCNQ1 and KCNE1. I Ks functions as a 'repolarization reserve' in the heart by providing extra current for ventricular action potential shortening during β‐adrenergic stimulation. There has been much debate about how KCNQ1 and KCNE1 traffic in cells, where they associate to form I Ks channels, and the distribution pattern of I Ks channels relative to β‐adrenergic signalling complex. We used experimental strategies not previously applied to KCNQ1, KCNE1 or I Ks, to provide new insights into these issues. 'Retention‐using‐selected‐hook' experiments showed that newly translated KCNE1 constitutively trafficked through the conventional secretory path to the cell surface. KCNQ1 largely stayed in the endoplasmic reticulum, although dynamic KCNQ1 vesicles were observed in the submembrane region. Disulphide‐bonded KCNQ1/KCNE1 constructs reported preferential association after they had reached cell surface. An in situ proximity ligation assay detected I Ks channels in surface sarcolemma but not t‐tubules of ventricular myocytes, similar to the reported location of adenylate cyclase 9/yotiao. Fluorescent protein‐tagged KCNQ1 and KCNE1, in conjunction with antibodies targeting their extracellular epitopes, detected distinct cell surface and cytoplasmic pools of both proteins in myocytes. We conclude that, in cardiomyocytes, KCNQ1 and KCNE1 traffic by different routes to surface sarcolemma where they assemble into I Ks channels. This mode of delayed channel assembly helps I Ks fulfil its function of repolarization reserve. Proteomic experiments revealed a novel KCNQ1 interactor, microtubule plus‐end binding protein 1 (EB1). EB1 dimer (active form) bound KCNQ1 and increased its surface level. An LQT1 mutation, Y111C, reduced KCNQ1 binding to EB1 dimer. Key points: In adult ventricular myocytes, the slow delayed rectifier ( I Ks ) channels are distributed on the surface sarcolemma, not t‐tubules. In adult ventricular myocytes, KCNQ1 and KCNE1 have distinct cell surface and cytoplasmic pools. KCNQ1 and KCNE1 traffic from the endoplasmic reticulum to the plasma membrane by separate routes, and assemble into I Ks channels on the cell surface. Liquid chromatography/tandem mass spectrometry applied to affinity‐purified KCNQ1 and KCNE1 interacting proteins reveals novel interactors involved in protein trafficking and assembly. Microtubule plus‐end binding protein 1 (EB1) binds KCNQ1 preferentially in its dimer form, and promotes KCNQ1 to reach the cell surface. An LQT1‐associated mutation, Y111C, reduces KCNQ1 binding to EB1 dimer.